The Position of the Principle of Legality in Law No. 1 of 2023 for the Development of Criminal Law in Indonesia - Nainggolan, Rani Oslina; Syahrin, Alvi; Mulyadi, Mahmud (State of Islamic Institute Langsa, 2024)
Ideally, the Principle of Legality serves as the fundamental basis in criminal law to ensure legal certainty and justice. However, in reality, with the enactment of Law No. 1 of 2023, there has been controversy regarding the evolving application of the law in Indonesia. The issue that arises is how this change impacts the application of criminal law, particularly in the context of protecting collective and individual interests. This study aims to analyze the position and consequences of the Principle of Legality in the development of criminal law in Indonesia. The method used is normative juridical research with a descriptive qualitative approach. The results of the study show that the Principle of Legality in Law No. 1 of 2023 emphasizes the principles of lex scripta, lex stricta, lex certa, and lex praevia, which reinforce legal certainty. The consequence of its application for the future of criminal law is the creation of a principle that is more adaptive and relevant to the diverse needs and culture of Indonesian society.